Insurance and Takaful Concepts: An Islamic Analysis and Offer in Life Assurance - Fuad Muhammad Zein; Anisa Rosdiana Zein; Afiq Miftahurizqi Alhaq (Muhammadiyah University Press, 2021)
This paper aims to provide a comparative analysis between the concept of insurance and the concept of takaful from an Islamic perspective. The method used in this paper is the study of libraries, in which the author seeks to find, summarize, analyze and ultimately deduce from various authoritative data sources. Insurance is a non-bank financial institution that offers protection against difficulties to the public. By paying dues or premiums that have been determined, the public has the right to make a claim that will be reimbursed by the insured party several funds that have also been determined. The insurer states to bear all risks that occur in the future. Therefore, all dues paid will be covered and managed by the company. However, it turns out that attitude is detrimental. Because the claim from the customer is not filed, then the customer's money is forfeited and entirely belongs to the company. In addition, the management of funds that are unclear and even almost unknown to customers makes this insurance practice illegal because it contains gharar and usury.